Analisis Pengaruh Penambangan Galian C Terhadap Lingkungan Perairan dan Sosial Ekonomi di Desa Kampung Pinang Kecamatan Perhentian Raja Kabupaten Kampar - Fadly Warisman Sitio; Zulfan Saam; Zulkifli Zulkifli (Berkala Perikanan Terubuk, 2015)
This study aimed to analyze the impact of type C surface mining materials at the river water environment parameters (flow velocity, depth, turbidity, temperature, water transparency, TSS, pH, DO and BOD5) and the social economic communityin Kampung Pinang village. The method was a survey where the water quality samples taken from 6 stations set with two repetitions then its value compared with the supporting literature, expert opinions and Government Regulation No. 82 of 2001. For the social economic aspects of the respondents conducted in-depth interviews. The results of this study showed the water temperature ranged from 29 - 29.5°C. Water transparency values ranging from 0.43 -  0.67 m. Turbidity values ranged from 54.4 - 61.8 NTU. Flow velocity values ranged from 0.07 - 0.25 m/sec. The depth of the river waters ranged from 2.4 - 8.4 m. TSS values ranged from 42.4 - 58.6 mg/l. Dissolved oxygen values ranged from 4.1 - 4.6 mg/l. The value of the degree of acidity (pH) is 6. Value BOD5 in river waters ranged from 3.1 - 3.7 mg/l. Based of the value of type C surface mining materials tends to affect the brightness, turbidity, depth and TSS. The impact also affects the equilibrium of the river that leads to large sediment transport, a decrease in the river bottom, sliding cliffs, changes the river morphology and pattern of current flow of the river. Social economic impact is a reduction in unemployment, an increase in income of the community, the presence of free time for family, increase cash income for the village, lack of job security led to accidents, reduced convenience of the public due to pollution and damage to the road and then the fear of the people on the banks of the river because of the potential for landslides.